Eighty - Les Peintres d'Europe : Allemagne - Belgique - Danemark - Espagne - Finlande - France - Grande Bretagne - Grèce - Hollande - Irlande - Italie - Luxembourg - Norvège - Portugal - Suède - Suisse. - Chalumeau, Jean-Luc (Paris : Eighty - Les Peintres d'Europe, 1987)
Alberola, Jean Michel ; Anderson, Jean Erik ; Armando ; Armleder, John ; Arroyo, Eduardo ; Biwer, Jean Marie ; Blais, Jean-Charles ; Blume, Anna ; Blume, Bernhard ; Book, Max ; Brennan, Cecily ; Broto, José-Manuel ; Bunk, Holger, Burri, Alberto ; Campano, Miguel-Angel ; Charlier, Jacques ; Chia, Sandro ; Christakis, Tassos ; Clément, Alain ; Clemente, Francesco ; Cognée, Philippe ; Combas, Robert ; Cronqvist, Léna ; Cucchi, Enzo ; Duchateau, Hugo ; Ocatave, Jean-François ; Vandenberg, Philippe ; etc.
Eighty - Les Peintres d'Europe, Ancienne Douane, Strasbourg, 29.01 - 28.02.1988
boek
Keywords: Europa